The Impact of Workplace Spirituality on Employee Performance - Sharifah Fazirah Syed Ahmad; Nur Arfifah binti Abdul Sabian; Nur Raihan Che Nawi (Information Management and Business Review, 2024)
The contemporary workplace, characterized by its rapid pace and dynamism, acknowledges the profound impact of work spirituality on employee productivity. This research explores the influence of spirituality in the workplace on employee performance through the examination of meaningful work, a sense of community, and organizational trust. Utilizing a quantitative approach with questionnaire distribution among academicians from business and management faculty at a local university in Selangor was conducted. Based on Pearson Correlation analysis, the result reveals a significant positive correlation between meaningful work, a sense of community, organizational trust, and employee performance. All hypotheses were accepted, indicating their positive influence. Moreover, Multiple Regression analysis highlights the substantial impact of workplace spirituality on employee performance. Practically, the study emphasizes aligning efforts for employee development with the recognized factors of workplace spirituality. In conclusion, organizations are urged to acknowledge and integrate spiritual elements in the workplace for a positive impact on employee performance.